Irradiated recycled plastic as a concrete additive for improved chemo-mechanical properties and lower carbon footprint. (January 2018) - Schaefer, Carolyn E.; Kupwade-Patil, Kunal; Ortega, Michael; Soriano, Carmen; Büyüköztürk, Oral; White, Anne E.; Short, Michael P.
Highlights: Irradiated recycled plastic as a concrete additive for improved properties. Micro and pore- structure analysis including XRD, SEM and X-ray tomography. Silica fume and fly ash help in densifying the cement paste with irradiated plastic. Abstract: Concrete production contributes heavily to greenhouse gas emissions, thus a need exists for the development of durable and sustainable concrete with a lower carbon footprint. This can be achieved when cement is partially replaced with another material, such as waste plastic, though normally with a tradeoff in compressive strength. This study discusses progress toward a high/medium strength concrete with a dense, cementitious matrix that contains an irradiated plastic additive, recovering the compressive strength while displacing concrete with waste materials to reduce greenhouse gas generation. Compressive strength tests showed that the addition of high dose (100 kGy) irradiated plastic in multiple concretes resulted in increased compressive strength as compared to samples containing regular, non-irradiated plastic. This suggests that irradiating plastic at a high dose is a viable potential solution for regaining some of the strength that is lost when plastic is added to cement paste. X-ray Diffraction (XRD), Backscattered Electron Microscopy (BSE), and X-ray microtomography explain the mechanisms for strength retention when using irradiated plastic as a filler for cement paste. By partially replacing Portland cement with a recycled waste plastic, this design may have a potential to contribute to reduced carbon emissions when scaled to the level of mass concrete production.